Determinación de las fases fenológicas y fenométricas e indice de balance hidríco en el cultivo de arroz (Oryza sativa) en condiciones de secano, cantón Portoviejo, provincia de Manabí - Manrique Anzules, Jairo Omar (2014)
In Portoviejo Canton, the research was carried out in order to understand the effects of climate change on lNlAP 15 And SFL-9 hybrids with two different fertilizations. The applied fertilizers were: the complete fertilization and the farmer’s fertilization with five repetitions. A complete randomized block design (CRBD) was used with factorial arrangement 2 x 4, being the factor A (Water rice) and the factor B (Fertilizers). Six replicates were used with twenty-four experimental units, the best treatment is resulted of the variables length, diameter, number of nodes, and height of plant. The hybrid SFL-9 presented the best measurements after 36 days with 90.30, 8.50, 4.77 and 95.83 cm....